Effect of Treatment on Steroidome in Women with Multiple Sclerosis - Hill, Martin; Kancheva, Radmila; Velíková, Marta; Kančeva, Ludmila; Včelák, Josef; Ampapa, Radek; Židó, Michal; Štětkářová, Ivana; Libertínová, Jana; Vosátková, Michala; Vítků, Jana; Kolátorová, Lucie; et al. (International journal of molecular sciences, 2025)
Multiple sclerosis (MS) is a chronic inflammatory neurodegenerative disease of the central nervous system. The manifestation of MS is related to steroid changes during the menstrual cycle and pregnancy. As data focusing on the effect of anti-MS drug treatment on steroidome are scarce, we evaluated steroidomic changes (79 steroids) in 61 female MS patients of reproductive age 39 (29, 47) years (median with quartiles) after treatment with anti-MS drugs on the GC-MS/MS platform and immunoassays (cortisol and estradiol). The changes were assessed using steroid levels and steroid molar ratios (SMRs) that may reflect the activities of steroidogenic enzymes (SMRs). A repeated measures ANOVA, followed by multiple comparisons and OPLS models, were used for statistical analyses. The anti-MS treatment decreased steroid levels in the follicular phase. Anti-CD20 monoclonal antibodies (mAb), such as ofatumumab and ocrelizumab; inhibitors of the sphingosine-1-phosphate receptor (S1PRI); and IFNβ-1a decreased circulating 17-hydroxy-pregnanes and shifted the CYP17A1 functioning from the hydroxylase- toward the lyase step. Decreased conjugated/unconjugated steroid ratios were found after treatment with anti-MS drugs, especially for glatiramer acetate and anti-CD20 mAb. In the luteal phase, IFN-β1a treatment increased steroidogenesis; both IFN-β1a and ocrelizumab increased AKR1D1, and S1PRI increased SRD5A functioning. Anti-CD20 mAb reduced the functioning of enzymes catalyzing the synthesis of immunomodulatory 7α/β and 16α-hydroxy-androgens, which may affect the severity of MS. The above findings may be important concerning the alterations in bioactive steroids, such as cortisol; active androgens and estrogens; and neuroactive, neuroprotective, and immunomodulatory steroids in terms of optimization of anti-MS treatment.
Keywords: menstruační cyklus; Steroids; Menstrual Cycle; Multiple Sclerosis; anti-MS drugs; steroidomics; multivariate statistics; Adult; Glatiramer Acetate; dospělí; multiple sclerosis; lidé; ženské pohlaví; Humans; glatiramer acetát; steroidy; GC-MS/MS; Female; lidé středního věku; roztroušená skleróza; Middle Aged